Titanium Dioxide Nanoparticles-Induced Genotoxic Effects in Mosquito Culex quinquefaciatus - Aastha Saini; Kanwaljit Kaur Ahluwalia; Amrik Singh Ahluwalia; Neelam Thakur; Puneet Negi; Abeer Hashem; Khalid F. Almutairi; Elsayed Fathi Abd_Allah (Toxics)
Titanium dioxide (TiO2) nanoparticles are being extensively used in a wide range of industrial applications for producing a variety of different consumer products, including medicines and even food items. The consumption of these products is increasing at an alarming rate, and this results in the release of these nanoparticles in the environment, causing a threat to organisms thriving in aquatic as well as terrestrial ecosystems. That is why screening such materials for their genotoxic effects, if any, becomes essential. A toxicity assay was performed to determine the LD20 of these nanoparticles for the mosquito Culex quinquefaciatus by Probit analysis. Early fourth instar larvae were exposed to the selected dose of 50 µg/mL, which is <LD20 value, for 24 h treatment. Chromosomal slides were prepared from lacto-aceto-orcein-stained gonads of adult mosquitoes developed from treated and control larvae. These nanoparticles were reported cytotoxic as a statistically significant decline in mitotic index in treated mosquitoes than controls were observed. The nanoparticles were also found to induce various structural and numerical chromosomal aberrations in the treated lot. In the end, it can be concluded that these nanoparticles do have a genotoxic effect. The present study provides a caution against further use of these nanoparticles. There must be the development of strategies for the safe, sustainable use as well as proper disposal of these nanoparticles so as to protect both biotic and non-biotic components of the environment.